Prediction of Future Land Use and Land Cover (LULC) in Makassar City - Sudirman Nganro; Slamet Trisutomo; Roland Barkey; Mukti Ali; Hidefumi Imura; Akio Onishi; Pei-I Tsai; Mohd Amirul Mahamud (TATALOKA, 2021)
Migration from rural area to urban area increases urban population. It increases and needs for settlements, leading to conversion of agricultural lands into settlement areas. Inconsistent land use compared with spatial planning causes change in land use. Spatial land use expansion can be monitored and predicted by modeling. NetLogo application is a software integrated with Agent-Based Modeling (ABM), which can be used to predict change of land use with various complex parameters. The present study used population growth as a parameter to predict change of land use of Makassar in 2050 based on 2017 land use classification map as the start of the prediction. The analysis result showed that the biggest change of land use happens to Settlement class which is 594.74 hectares and the smallest is Water Body class which is 8.76 hectares.